Ernest Hemingway : a new life - Hutchisson, James M. (University Park, Pennsylvania : The Pennsylvania State University Press, 2016)
"A biography of Ernest Hemingway that places his life and art in the defining contexts of the women and places that were important to him, and the pattern of mental illness and suicide in his family"--Provided by publisher.
Introduction -- The Midwest : Childhood and Youth -- Italy and Agnes von Kurowsky -- Michigan, Chicago, and Hadley -- Paris -- Duff Twysden and The Sun Also Rises -- Pauline, Key West, and A Farewell to Arms -- Spain and Death in the Afternoon -- Jane Mason and Africa -- Martha Gellhorn and the Spanish Civil War -- Cuba and For Whom the Bell Tolls -- China and World War II -- Mary, Adriana, and Across the River and into the Trees -- Revisiting the Past : Africa and Paris -- Dangerous Summers : Spain, Cuba, Idaho.
Includes bibliographical references and index.
Keywords: Hemingway, Ernest, -- 1899-1961.; Authors, American -- 20th century -- Biography